2016
DOI: 10.1111/1440-1681.12619
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐linked differences in the course of chronic kidney disease and congestive heart failure: a study in 5/6 nephrectomized Ren‐2 transgenic hypertensive rats with volume overload induced using aorto‐caval fistula

Abstract: The role of hypertension and the renin-angiotensin system (RAS) in sex-related differences in the course of chronic kidney disease (CKD) and congestive heart failure (CHF) remain unclear, especially when the two diseases are combined. In male and female Ren-2 transgenic rats (TGR), a model of hypertension with activation of endogenous RAS, CKD was induced by 5/6 renal mass reduction (5/6 NX) and CHF was elicited by volume overload achieved by creation of an aorto-caval fistula (ACF). The primary aim of the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 60 publications
(165 reference statements)
3
22
0
Order By: Relevance
“…The beneficial effects of the treatment, particularly on the survival rate, were more pronounced in ACF FHH rats. In addition, our results show that, in accordance with previous findings (Oliver-Dussault et al, 2010; Melenovsky et al, 2012, 2018; Červenka et al, 2015, 2016; Kala et al, 2018), after creation of ACF the animals displayed signs of pronounced cardiac hypertrophy, involving both ventricles. Remarkably, this was associated with distinct lung congestion, indicating LV failure without signs of RV failure (no liver congestion).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The beneficial effects of the treatment, particularly on the survival rate, were more pronounced in ACF FHH rats. In addition, our results show that, in accordance with previous findings (Oliver-Dussault et al, 2010; Melenovsky et al, 2012, 2018; Červenka et al, 2015, 2016; Kala et al, 2018), after creation of ACF the animals displayed signs of pronounced cardiac hypertrophy, involving both ventricles. Remarkably, this was associated with distinct lung congestion, indicating LV failure without signs of RV failure (no liver congestion).…”
Section: Discussionsupporting
confidence: 93%
“…Animals underwent either sham-operation or ACF creation as described above (at the week labeled -4) and were left without treatment for 4 weeks. Previous studies have shown that after this time CHF features are fully developed but the animals are still in the compensation phase (Oliver-Dussault et al, 2010; Melenovsky et al, 2012, 2018; Červenka et al, 2015, 2016; Kala et al, 2018). At this time point (week 0) the rats were divided into the following experimental groups:…”
Section: Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…The rat with aorto-caval fistula (ACF) presents a well-defined model of CHF dependent on volume overload, characterized also by activation of the systemic and intrarenal RAS, signs of cardiac remodeling as well as congestion and impairment of renal function. Thus, in many aspects the model reproduces the course of CHF in untreated human patients 2124,3035 .…”
Section: Introductionmentioning
confidence: 89%
“…The hypertensive rat transgenic for the mouse Ren-2 renin gene [TGR; strain name TGR(mRen2)27] presents a unique angiotensin II (ANG II)-dependent model of hypertension in which its development is attributed to a single gene alteration and to the augmented activation of endogenous RAS 3638 . Thus, an experimental model of CHF that combines the well-recognized crucial detrimental factors promoting the progression of CHF is available and we have recently shown ACF TGR exhibit markedly increased CHF-related mortality as compared with the course in ACF Hannover Sprague-Dawley (HanSD) rats (transgene-negative, normotensive controls to TGR) 23,35 . We found that in addition to the increased RAS activity, ACF TGR also displayed tissue deficiency of biologically active fatty acid epoxides due to increased conversion of epoxyeicosatrienoic acids (EETs) [biologically active metabolites of cytochrome P450 (CYP)-dependent epoxygenase pathway of arachidonic acid (AA)] by soluble epoxide hydrolase (sEH) to biologically inactive dihydroxyeicosatrienoic acids (DHETEs).…”
Section: Introductionmentioning
confidence: 99%